KUALITAS KINERJA PEGAWAI BIDANG PEMBINAAN SMA PADA DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI SULAWESI TENGAH - Pratiwi, Retno; Mangansing, Nasir; Daswati, Daswati (Katalogis, 2019)
This study is about the Quality of High School Employee Performance at the Education and Culture Office of Central Sulawesi Province. In this study using descriptive qualitative research with a number of 8 informants who were deliberately selected, namely the Head of High School Development Section, Head of High School Facilities and Infrastructure Section, 1 High School Facilities and Infrastructure Section staff, Head of Institutional and Curriculum Section, 1 Institutional Section staff and Curriculum, Head of High School Student Section, and 1 High School Student Section staff, High School PTK Section head. The theory used is the theory of Agus Dwiyanto, namely productivity, service quality, responsiveness, responsibility, and accountability. Observations and documents are also carried out to get the data needed. The results of the study showed that the High School Field Development Performance at the Education and Culture Office of Central Sulawesi Province had not been maximized. This is based on the results of research with 5 aspects that are used as benchmarks in research, only two focus studies are fulfilled, namely the responsibility and accountability indicators. Whereas from productivity indicators, it has not been said to be optimal because of lack of technical human resources and the participation of apparatus is still lacking. While the Service Quality Indicators are said to be not optimal because there is still a lack of facilities and infrastructure to support service activities. Likewise, the Indicator of Responsiveness has not yet been said to be optimal because the facilities and infrastructure have also become obstacles in responding to the world community of education.